2013
DOI: 10.5713/ajas.2013.13241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Electrolyte Balance on Growth Performance, Nitrogen Metabolism and Some Blood Biochemical Parameters of Growing Rabbits

Abstract: The effects of different dietary electrolyte balance (DEB) on growth performance, nitrogen (N) metabolism and some blood biochemical parameters were investigated in 2 to 3 months old growing rabbits. A total of 150 growing rabbits of 2 months age were randomly divided into five groups according to average body weight, with 30 rabbits in each group. The DEB levels of the five experimental diets were −154, −3.16, +201, +347, and +500 meq/kg of dry matter (DM), respectively. There was a 7-d adaptation period and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Escobosa et al (1984) found that dietary sodium bicarbonate during heat stress increased blood glucose level of cows and they reported that this increase may be due to higher feed intake in high sodium bicarbonate group. Li et al (2013) found that increasing DEB level in rabbits' diet (up to 500 meq) increased feed intake, N metabolism and blood total protein. It has been reported that blood proteins play a basic role of intracellular buffers within the body tissues to provide a reserve buffering capacity (Cunningham, 2002) and this is indicated that increasing blood total protein concentrations by DEB supplementation had a beneficial effect on acid-base balance.…”
Section:  Metabolic Ratementioning
confidence: 94%
“…Escobosa et al (1984) found that dietary sodium bicarbonate during heat stress increased blood glucose level of cows and they reported that this increase may be due to higher feed intake in high sodium bicarbonate group. Li et al (2013) found that increasing DEB level in rabbits' diet (up to 500 meq) increased feed intake, N metabolism and blood total protein. It has been reported that blood proteins play a basic role of intracellular buffers within the body tissues to provide a reserve buffering capacity (Cunningham, 2002) and this is indicated that increasing blood total protein concentrations by DEB supplementation had a beneficial effect on acid-base balance.…”
Section:  Metabolic Ratementioning
confidence: 94%
“…At the beginning of the experiment, the initial body weight, daily feed intake and the number of rabbits with diarrhoea were recorded. At the end of the experiment, the terminal weight was recorded, and the average daily feed intake (ADFI), average daily gain (ADG) and feed gain ratio (F/G) were calculated (Du et al 2013;Li et al 2013). The numbers of rabbits with diarrhoea or that died were recorded daily throughout the study.…”
Section: Analysis Of Production Performancementioning
confidence: 99%